LO065: Reduced length of stay and adverse events using Bier block for forearm fracture reduction in the pediatric emergency department. (2nd June 2016) - Fauteux-Lamarre, E.; Burstein, B.; Cheng, A.; Bretholz, A.
Abstract : Introduction: Distal forearm fractures are one of the most common injuries presenting to the pediatric emergency department. Procedural sedation (PS) is commonly used to provide analgesia during fracture reduction, but requires a prolonged recovery period and can be associated with adverse respiratory events. Bier block (BB) regional anesthesia is a safe alternative to PS for fracture reduction analgesia. We sought to assess the impact of BB on length of stay (LOS) and adverse events following forearm fracture reduction compared to PS.Methods: We performed a retrospective study of patients aged 6 to 18 years, presenting with forearm fractures requiring closed reduction from June 2012 to March 2014. The primary outcome measure was emergency department LOS; secondary outcomes included reduction success rates, adverse events and unscheduled return visits.Results: Two-hundred and seventy-four patients were included for analysis; 109 treated with BB, 165 underwent PS. Overall, mean LOS was 82 min shorter for patients treated in the BB group (279 min vs. 361 min, p<0.05). Sub-analysis revealed a reduced LOS among patients treated with BB for fractures involving a single bone (286 min vs. 388 min, p<0.001) and both-bones of the forearm (259 min vs. 321 min, p<0.05). Both BB and PS resulted in comparable rates of successful reduction (98.2% vs. 97.6%, p=0.74). There were no major adverse events in either group. Patients who received BB experienced significantly fewer minor adverse events (2.7% vs. 14.5%, p<0.05). Return visit rates were similar in the BB and PS groups (17.6% vs. 17.1%, p<0.05).Conclusion: Compared to PS, forearm fracture reduction performed with BB was associated with a reduced emergency department LOS and fewer adverse events, with no difference in reduction success or return visits.